Gum Arabic as corrosion inhibitor in the oil industry: experimental and theoretical studies. (4th July 2019) - Shen, Chen; Alvarez, Victor; Koenig, Josh D. B.; Luo, Jing-Li
ABSTRACT: Corrosion inhibitors are commonly used in the oil industry due to their effectiveness, easy application and relatively low cost. Electrochemical and molecular simulation methods were used to investigate the application of Gum Arabic (GA) as a natural polymer corrosion inhibitor for carbon steel. The Tafel analysis results showed that GA works as a mixed-type corrosion inhibitor on carbon steel with the increased Open Circuit Potential. In synthetic brine, the adsorption isotherm study showed that GA inhibitor films were mainly formed via chemisorption. The corrosion efficiency of GA measured by polarisation curve, polarisation resistance and impedance measurements, were 94.0, 83.5 and 90%, respectively. Molecular simulations studies indicated that high molecular weight of carbohydrates have strong interaction with Fe (111) surface.